2013
DOI: 10.5194/isprsannals-ii-2-w1-299-2013
|View full text |Cite
|
Sign up to set email alerts
|

Towards Precise Metadata-set for Discovering 3D Geospatial Models in Geo-portals

Abstract: ABSTRACT:Accessing 3D geospatial models, eventually at no cost and for unrestricted use, is certainly an important issue as they become popular among participatory communities, consultants, and officials. Various geo-portals, mainly established for 2D resources, have tried to provide access to existing 3D resources such as digital elevation model, LIDAR or classic topographic data. Describing the content of data, metadata is a key component of data discovery in geo-portals. An inventory of seven online geo-por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although digital libraries hold the power to create an easily accessible repository of fossil data, removing geographic barriers, and preserving the integrity of fossils, such a library poses unique problems due to the nature of the data. These problems include how to catalogue, acquire, and preserve the data in addition to how to protect the rights of those who create and own the data (Berquist et al, 2012;Boyer et al, 2017;Davies et al, 2017;Hardesty et al, 2020;Skinner et al, 2013;Ulguim, 2018;Zamyadi et al, 2013). Literature about previous and existing digital fossil libraries, and similar digital libraries containing 3D data, provides important insight into how to create, maintain, and grow a repository of 3D fossil data moving forward.…”
Section: Trends and Challenges In 3d Digital Librariesmentioning
confidence: 99%
“…Although digital libraries hold the power to create an easily accessible repository of fossil data, removing geographic barriers, and preserving the integrity of fossils, such a library poses unique problems due to the nature of the data. These problems include how to catalogue, acquire, and preserve the data in addition to how to protect the rights of those who create and own the data (Berquist et al, 2012;Boyer et al, 2017;Davies et al, 2017;Hardesty et al, 2020;Skinner et al, 2013;Ulguim, 2018;Zamyadi et al, 2013). Literature about previous and existing digital fossil libraries, and similar digital libraries containing 3D data, provides important insight into how to create, maintain, and grow a repository of 3D fossil data moving forward.…”
Section: Trends and Challenges In 3d Digital Librariesmentioning
confidence: 99%
“…Additionally, Biljecki et al [4] found that the modelling choices made by practitioners when acquiring, processing and utilising 3D city models are rarely documented in the metadata of a dataset, often because there is no way to store this information. This information is necessarily not only for dataset discovery but also to ensure interoperability between various 3D city models [26].…”
Section: D Geospatial Metadata Needsmentioning
confidence: 99%
“…The ease comes from reducing the need for data users to individually parse every file they encounter. Zamyadi et al [26] state that metadata for 3D geoinformation is very different from one online portal to another and even for 3D datasets within the same portal. Furthermore the integration of 3D datasets within traditional 2D portals is difficult because 2D portals do not contain specific and common metadata categories and attributes required by 3D datasets [26].…”
Section: Resource/data Discoverymentioning
confidence: 99%
See 2 more Smart Citations